A hospital-based study on knowledge, attitude and practice of pregnant women on gender preference, prenatal sex determination and female feticide at tertiary care hospital, Bikaner - Mehta, Seema; Meena, Rattiram; Acharya, Rekha; Sharma, Gaurav; Bhatt, Madhu Patni (International Journal Of Community Medicine And Public Health, 2017)
Background: Female feticide has been a big social problem in all the states of India. There is a male child preference by pregnant women including their family members. Thus this study aimed to assess attitude and awareness on female feticide. Methods: The present study was conducted in ANC center of Medical college Hospital, Bikaner of Rajasthan in 500 pregnant women (250 rural and 250 Urban). Results: Out of 500 pregnant women 62% had shown no gender preference, 23% preferred male child and 15% had preferred to have female child. Regarding awareness, 88% and 90% women knew that prenatal sex determination and female feticide are illegal respectively. Conclusions: Being the civilized citizens, it is our duty to raise voice against the declining sex ratio and killing of girl child. Being a woman it is our primary duty as well as concern to come forward to stop this menace.